1998
DOI: 10.1074/jbc.273.44.28813
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Distance Measurements Reveal an (αβ)2Dimeric Structure of Na+/K+-ATPase

Abstract: ATP hydrolysis by Na؉ /K ؉ -ATPase proceeds via the interaction of simultaneously existing and cooperating high (E 1 ATP) and low (E 2 ATP) substrate binding sites. It is unclear whether both ATP sites reside on the same or on different catalytic ␣-subunits. To answer this question, we looked for a fluorescent label for the E 2 ATP site that would be suitable for distance measurements by Fö rster energy transfer after affinity labeling of the E 1 ATP site by fluorescein 5-isothiocyanate (FITC). Naϩ /K ϩ -ATPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 60 publications
2
24
1
Order By: Relevance
“…Fluorescence resonance energy transfer measurements between bound FITC and bound ErITC indicated that the two probes were too far apart to be bound to the same protomer (11). ATP at high concentration prevented the binding of ErITC to the FITC-labeled enzyme (11). Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Fluorescence resonance energy transfer measurements between bound FITC and bound ErITC indicated that the two probes were too far apart to be bound to the same protomer (11). ATP at high concentration prevented the binding of ErITC to the FITC-labeled enzyme (11). Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The putative low affinity ATP binding site resides on the same ␣ chain as the putative high affinity ATP binding site. -ATPase with about half-maximal theoretical phosphorylation capacity binds about 0.5 FITC molecules per ␣␤ protomer and then binds an additional 0.5 molecules of ErITC per ␣␤ protomer to the FITC-labeled enzyme with inhibition of the residual K ϩ -dependent pNPPase activity (11). In this calculation, the entire protein mass of the Na ϩ ,K ϩ -ATPase preparation was taken to consist only of ␣␤ protomers although only half could be phosphorylated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 and 8. Briefly, physical interactions between ␣␤, ␣␣, and ␤␤ have been implicated from cross-linking studies (14,16,24,(37)(38)(39), co-immunoprecipitations have demonstrated the interaction of different ␣-subunit isoforms (19), thermal inactivation studies suggest ␣␣ contact (18), fluorescence resonance energy transfer provides distance measurements consistent with (␣␤) 2 (40), and low angle laser light scattering photometry coupled with high performance gel chromatography (41) as well as single molecule detection (17) indicate the presence of ␣␤, (␣␤) 2 , and higher order oligomers. Numerous studies in which half-site phosphorylation and halfor quarter-site ATP-analog binding stoichiometries have been interpreted in a model that proposes that the Na,K-ATPase co-exits simultaneously in the E1ATP, E2ATP, or EPATP forms (42).…”
Section: Resultsmentioning
confidence: 99%